The pioneering research activity of Georg Gottlieb Pusch on the Middle Miocene of Poland and present-day western Ukraine - Studencka, Barbara (Acta Geologica Polonica, 2026)
This paper shows that Georg Gottlieb Pusch (1790–1846), the most outstanding Polish geologist of the 19th century, was the author of the first catalogue of Middle Miocene fossils from the territories of the then Kingdom of Poland (1815–1832) and Eastern Galicia (now south-eastern Poland and western Ukraine). This catalogue, containing 400 species-level names, was published in the second volume of the monumental treatise, i.e., Geognostische Beschreibung von Polen, about the geology of Poland (Pusch 1836). Out of the 137 species-level names of bivalves, five were introduced as new: Venericardia annulata, Astarte crassatellaeformis, Cardium gracile, Venericardia lima, and Pecten nodosiformis. All newly described species were subsequently re-described and illustrated in the comprehensive volume Polens Paläontologie devoted to the palaeontology of Poland, in which Pusch (1837a) included descriptions of three new taxa: Mactra biangulata, Pecten lilli, and Pecten Burdigalensis var. polonica, as well as a revised list of the Middle Miocene fauna of Poland, Volhynia and Podolia, previously published in the Geognostische Beschreibung von Polen. In the present work the taxa described by Pusch (1836, 1837a) have been critically revised. The species Cardium gracile Pusch, 1836, Pecten nodosiformis Pusch and de Serres in Pusch, 1836, and Pecten lilli Pusch, 1837 are considered taxonomically valid. Astarte crassatellaeformis Pusch, 1836 is newly synonymized with the present-day Venus foliaceolamellosa Dillwyn, 1817. Venericardia annulata Pusch, 1836 and Venericardia lima Pusch, 1836 are regarded as nomina dubia. The names Pecten Burdigalensis var. polonica Pusch, 1837 and Mactra biangulata Pusch, 1837 are recognised as nomina oblita. In addition, it has been shown that an approach to knowledge about the rhodolith-bearing sediments of southern Poland began in the 1820s with the works of Georg Gottlieb Pusch, who is also the author of modern geological maps and the first profiles of the Middle Miocene sediments from the Kingdom of Poland and Eastern Galicia. Finally, Pusch’s position regarding the age of the gypsum deposits of the Nida River region is presented.